2021
DOI: 10.3390/microorganisms9061331
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity and Composition of Nitrate-Reducing Microbiomes from a Full-Scale Woodchip Bioreactor Treating Agricultural Drainage Water

Abstract: Denitrifying woodchip bioreactors (WBR), which aim to reduce nitrate (NO3−) pollution from agricultural drainage water, are less efficient when cold temperatures slow down the microbial transformation processes. Conducting bioaugmentation could potentially increase the NO3− removal efficiency during these specific periods. First, it is necessary to investigate denitrifying microbial populations in these facilities and understand their temperature responses. We hypothesized that seasonal changes and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…These dominant phyla included Proteobacteria, Firmicutes, Chloroflexi, Actinobacteria, and Bacteroidetes. The observation that dominant phyla include Proteobacteria, Actinobacteria, and Bacteroidetes is consistent with other studies (Grießmeier et al., 2017; Hellman et al., 2021; Jéglot, Sørensen, et al., 2021). Firmicutes have also been observed as a dominant phylum at the laboratory scale (Grießmeier et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…These dominant phyla included Proteobacteria, Firmicutes, Chloroflexi, Actinobacteria, and Bacteroidetes. The observation that dominant phyla include Proteobacteria, Actinobacteria, and Bacteroidetes is consistent with other studies (Grießmeier et al., 2017; Hellman et al., 2021; Jéglot, Sørensen, et al., 2021). Firmicutes have also been observed as a dominant phylum at the laboratory scale (Grießmeier et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the resulting ammonium levels in the water after barrier passage is not lower in the compost barriers despite significantly higher amoA abundances. In other woodchip-based systems for N removal, it has been shown that changes in the microbial community composition appear within a few months ( Grießmeier et al, 2017 ; Aalto et al, 2020 ; Hellman et al, 2021 ; Jéglot et al, 2021 ). Given that the increase in copy numbers of nir and nosZ genes in the woodchip barrier resulted in the same genetic potential for denitrification and nitrous oxide reduction between the compost and woodchip barriers, it is plausible that in the present systems, the potentials for denitrification and nitrous oxide reduction were similar among the barriers during a substantial part of the experimental period, which contributed to the equal overall removal of reactive N. A higher temporal resolution would be needed to better understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them can breakdown cellulose, a major component of woodchips, and therefore, can provide more labile carbon to the environment (Jang et al, 2019). By inoculating these cold-adapted denitrifiers, it might be possible to enhance nitrate removal at cold conditions (Jéglot et al, 2021, 2022).…”
Section: Introductionmentioning
confidence: 99%